Establishment and application of a one-step multiplex real-time PCR assay for detection of A, B, and C subtypes of avian metapneumovirus - Mingjun Su; Jiongze Cheng; Xiangwen Xu; Yijia Liu; Yulin Zhao; Yutao Wang; Xiaoxu Du; Jiale Ying; Junfang Yan; Huihua Zheng; Changyong Cheng; Jing Sun (Poultry Science)
Avian metapneumovirus (aMPV) represents a significant threat to the poultry industry, exhibiting a high degree of genetic diversity. Of these, the aMPV types A (aMPV-A), B (aMPV-B) and C (aMPV-C) are frequently detected in Chinese waterfowl and live poultry markets. Therefore, the rapid and accurate identification of these subtypes is of paramount importance in order to halt the spread of the disease. In this study, we have developed a multiplex real-time PCR assay endowed with the capacity to simultaneously discriminate aMPV-A, aMPV-B, and aMPV-C. This method demonstrates remarkable specificity, selectively amplifying aMPV-A, aMPV-B, and aMPV-C without cross-reactivity with other common avian pathogens. Furthermore, this method exhibits high sensitivity, with a detection threshold of 8.5 × 102 copies/μL for aMPV-A, aMPV-B, and aMPV-C. Moreover, the assay demonstrates reproducibility, as evidenced by intra- and inter-assay variability, with a coefficient of variation between 0.21% and 1.91%. Additionally, the receiver operating characteristic (ROC) curve analysis demonstrated that the multiplex real-time PCR assay exhibited high specificity and sensitivity (100.0% and 100.0% for aMPV-A, 90.9% and 100.0% for aMPV-B, 100% and 96.8% for aMPV-C) when compared with the classical aMPV real-time RT-PCR. Analyses of field samples (n=105) using the multiplex real-time PCR assay indicated that 35.2% (37/105) of samples were positive for aMPV, of which 29.7% (11/37) for aMPV-A, 32.4% (12/37) for aMPV-B and 37.8% (14/37) for aMPV-C. These data demonstrated that the multiplex real-time PCR assay can be used for epidemiological investigations of tree subtypes of aMPV and that aMPV had been observed to exhibit a proclivity for multiple types of co-infection in the Zhejiang province of China.